Assessment of the level of terminological competence of physical education teachers as the basis of professional activity - Красова, Інна; Дейнеко, Альфія; Марченков, Михайло; Луценко, Лариса (Slobozhanskyi Herald of Science and Sport, 2018)
Inna Krasova, Alfiya Deyneko, Mykhailo Marchenkov & Larysa Lutsenko Сonditions of modern interpretation of the learning process require an increasing role of the teacher and a lesson in physical culture. The normative requirements for the teacher already form a new approach to the teaching of physical culture, where the culture of communication and the level of cultural and professional competence of the teacher of physical culture occupy an important place, which, of course, is impossible without the knowledge and skillful use of gymnastic terminology. Purpose: identification of the level of terminological competence of teachers of physical culture, peculiarities of using terms, reasons that prevent teachers from effectively using gymnastic terminology during their professional activities. Material & Methods: in the study participated teachers of physical culture (n=87). Results: certain features of the use of gymnastic terminology by teachers of physical culture are examined. They found they lacked a level of terminological competence during their professional activities when using physical exercises. The reasons not allowing teachers of physical training to effectively use gymnastic terminology are revealed. Conclusions: level of terminological competence of each specialist is individual and very often requires its increase. It is established that despite the important role of using gymnastic terminology, its component in the lesson of physical culture decreases every year. A number of reasons have been identified that affect the level of terminological competence of teachers and are reflected in the quality of professional activity in general.